IMPACTS OF ANXIETY ON LEARNING: : FAMILY SCOPE AND SCHOOL SCOPE - Henrique Oliveira da Silva, Lucas (Revista Gênero e Interdisciplinaridade, 2021)
When a child moves from a familiar environment and enters the school environment, he leaves his comfort zone, bringing with him all his psychosocial load already acquired in the womb, family life and in his home environment, and moves to a highly social environment that it is the school that is an extremely stressful environment. Its main objective is socialization, but there are pre-existing factors that favor it not lowering this socialization. Taking into account the pedagogical and psychological principles, some anxiety classifications that the child can go through in this transition period were reviewed. A questionnaire was used to obtain data experienced by the interviewees. 10 children were evaluated: 5 males and 5 females, aged between 5 and 10, and 4 adults: 2 females and 2 males. A large part of the interviewees raised plausible arguments about the personalized themes. Encouraging the strengthening of knowledge about anxiety in early childhood education.